2019
DOI: 10.1101/621003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leptin and adiponectin correlations with body composition and lipid profile in children with Autism Spectrum Disorder

Abstract: Leptin and adiponectin have effects on the regulation of appetite and body composition, but evidence of these relationships in children is still limited. Even though investigations of their role in children with ASD are incipient, the nutritional aspects and eating difficulties that these patients may present are increasingly highlighted, often leading to inadequate nutritional status. This cross-sectional controlled study investigated the levels of adipokines in ASD children in comparison with healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…There are few studies in the literature comparing lipid profile levels in children with ASD with those in healthy children. Some of these studies have reported findings comparable to ours, demonstrating that serum cholesterol levels in children with ASD are elevated [32], whereas others demonstrate that serum cholesterol levels are lowered [33] or show no significant difference [34]. The first factor to consider when evaluating lipid profiles in children with ASD is gender.…”
Section: Discussionsupporting
confidence: 64%
“…There are few studies in the literature comparing lipid profile levels in children with ASD with those in healthy children. Some of these studies have reported findings comparable to ours, demonstrating that serum cholesterol levels in children with ASD are elevated [32], whereas others demonstrate that serum cholesterol levels are lowered [33] or show no significant difference [34]. The first factor to consider when evaluating lipid profiles in children with ASD is gender.…”
Section: Discussionsupporting
confidence: 64%
“…This hormone has an important role in the regulation of food intake and body weight [ 36 ], and its expression by adipose tissue is also influenced by feeding behavior [ 37 ]. In Castro’s study [ 38 ] ASD participants showed higher levels of leptin in comparison with typically developing children, and a positive correlation between leptin and fat mass was demonstrated, bringing out the role of leptin as a marker of adiposity in ASD children. Initially, the adipokines, hormones synthesized mainly by the adipocytes, were associated with eating disorders and obesity but later studies showed their important role in the regulation of immune responses and inflammation; for this reason, their involvement in the pathophysiology of autism was hypothesized [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, leptin shares structural and functional similarities with several cytokines, many of which are involved in neurodevelopment, including IL-6 and IL-12 [ 43 ]. The inverse relationship between leptin and 25(OH)D levels found in our study could be related to the fact that the leptin levels are regulated by 25(OH)D. In particular, 25(OH)D may directly affect the expression of leptin, reducing its release from adipose tissue and consequently decreasing tissue inflammation through the inhibition of NF-kB signaling [ 38 ]. It has also recently been demonstrated that 25(OH)D affects brain serotonin concentrations, and may control leptin levels [ 44 ].…”
Section: Discussionmentioning
confidence: 99%